2016
DOI: 10.1038/srep32780
|View full text |Cite
|
Sign up to set email alerts
|

Molecular organization, localization and orientation of antifungal antibiotic amphotericin B in a single lipid bilayer

Abstract: Amphotericin B is a popular antifungal antibiotic, a gold standard in treatment of systemic mycotic infections, due to its high effectiveness. On the other hand, applicability of the drug is limited by its considerable toxicity to patients. Biomembranes are a primary target of physiological activity of amphotericin B and both the pharmacologically desired and toxic side effects of the drug relay on its molecular organization in the lipid phase. In the present work, molecular organization, localization and orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 41 publications
6
58
1
1
Order By: Relevance
“…Despite several decades of clinical use, AmB mechanism of action at the molecular level remains elusive and several models have been proposed based on extensive experimental research and theoretical studies [45][46][47][48]54,55,[58][59][60][61][62][63][64][65][66]. AmB has been shown to bind sterol-containing membranes of eukaryotic cells and to insert into the lipid bilayer forming pore-like supramolecular structures that can act as transmembrane ion channels, leading to increased membrane permeability, K + leakage, and disruption of ion transport [44,45,48,53].…”
Section: Amphotericin B Properties and Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several decades of clinical use, AmB mechanism of action at the molecular level remains elusive and several models have been proposed based on extensive experimental research and theoretical studies [45][46][47][48]54,55,[58][59][60][61][62][63][64][65][66]. AmB has been shown to bind sterol-containing membranes of eukaryotic cells and to insert into the lipid bilayer forming pore-like supramolecular structures that can act as transmembrane ion channels, leading to increased membrane permeability, K + leakage, and disruption of ion transport [44,45,48,53].…”
Section: Amphotericin B Properties and Mode Of Actionmentioning
confidence: 99%
“…AmB has been shown to bind sterol-containing membranes of eukaryotic cells and to insert into the lipid bilayer forming pore-like supramolecular structures that can act as transmembrane ion channels, leading to increased membrane permeability, K + leakage, and disruption of ion transport [44,45,48,53]. Recent studies also suggest that different oligomerization of AmB in lipid bilayers modulated by membrane sterols contribute to the higher toxicity of the drug to fungal cells, since it has been found that ergosterol promotes association of AmB dimers into tetramers responsible for membrane permeabilization while cholesterol hinders AmB aggregation in the lipid matrix [44,46,48,55,62]. Disruption of ergosterol biosynthesis is responsible for resistance to Due to its amphipathic nature, AmB is able to self-associate in aqueous solution forming water soluble dimers and oligomers that can further associate to form insoluble polyaggregates, which act as a monomer reservoir [25,[43][44][45][46].…”
Section: Amphotericin B Properties and Mode Of Actionmentioning
confidence: 99%
“…2b (A1G cells) are preferentially formed in the environment of cholesterol and possibly contain the sterol as an element of such structures. It has been demonstrated that presence of either ergosterol or cholesterol in the lipid membranes was necessary for incorporation of AmB into the hydrophobic core of the membranes [43]. In the case of the MMG cells exposed to AmB, an increase of the fluorescence anisotropy can be observed (Fig.…”
Section: Flim Imaging Reveals Specific Amb Structures In A1g Cellsmentioning
confidence: 89%
“…A relatively intense fluorescence signal in the cell surface region, characterized by a long fluorescence lifetime (> 6 ns), coded with red color (Fig. 2b, upper panels), can be assigned to antiparallel dimeric structures of AmB [43,44]. The same structures are characterized by relatively low fluorescence anisotropy values (see the bottom panels in Fig.…”
Section: Flim Imaging Reveals Specific Amb Structures In A1g Cellsmentioning
confidence: 99%
See 1 more Smart Citation